LEGAL RESPONSIBILITIES OF THIRD PARTIES AND HOSPITALS REGARDING THE IMPLEMENTATION OF ELECTRONIC MEDICAL RECORDS - Maisyarah Mufrizal, Fhika; Risdawati, Irsyam; Rahmayanti, Rahmayanti (Universitas Efarina, 2024)
Medical records are simply a history of health services and illnesses faced by patients. The use of electronic medical records is predicted to be the most effective method of reducing errors, improving the quality of health services, and reducing costs. With the recommendation for the use of electronic medical records, many health service providers are implementing electronic medical records in an effort to improve service quality, increase patient satisfaction, and reduce medical errors. In Minister of Health Regulation no. 269 of 2008 Chapter II article 2 states that: (1) Medical records must be made in writing, complete and clear or electronically. (2) The administration of medical records using electronic information technology is further regulated by separate regulations. Before the issuance of Regulation of the Minister of Health of the Republic of Indonesia Number 24 of 2022 concerning Medical Records. The problem arises that to create an electronic medical record system, hospitals must entrust people or institutions who are competent to create a medical record system that can be accessed electronically. What about the confidentiality of the medical record history contained in it, can the third-party company access the electronic medical record system easily? Using normative juridical research methods, the author explores and learns from various sources the rules regarding the legal responsibilities of third parties and hospitals regarding the implementation of Electronic Medical Redord. The conclusion from this research is that in fact third parties are free from legal responsibility if later problems arise such as system leaks from the system that has been built. Please note that the warranty or maintenance period has passed, and the third party's connection cannot be proven.